2002
DOI: 10.1006/jcat.2001.3427
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Surface Vanadia Forms on V/Ti–Oxide Catalyst via Temperature-Programmed Reduction in Hydrogen and Spectroscopic Methods

Abstract: Surface vanadia species formed on vanadia/titania catalysts consisting of 0.2-2.6 monolayers (ML) of VO x have been characterized by FT-Raman spectroscopy under controlled atmosphere, temperature-programmed reduction in hydrogen (TPR), and solubility in diluted HNO 3 . Three types of species were observed with the maximum peak temperatures as follows: isolated monomeric species (≤770-780 K), polymeric species (810 K), and bulk amorphous V 2 O 5 (852 K). During the reduction, the V= =O bond of the monomeric spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
58
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 41 publications
9
58
1
Order By: Relevance
“…The peak is very similar to that obtained by reduction with hydrogen at 673 K. 9 The step of catalyst re-oxidation was performed by introduction of O 2 in the DRIFTS cell after purging with Ar. This operation led to rapid formation of new bands in the carbonyl region (Fig.…”
supporting
confidence: 64%
“…The peak is very similar to that obtained by reduction with hydrogen at 673 K. 9 The step of catalyst re-oxidation was performed by introduction of O 2 in the DRIFTS cell after purging with Ar. This operation led to rapid formation of new bands in the carbonyl region (Fig.…”
supporting
confidence: 64%
“…It was found that vanadia on a titania surface forms different types of structures depending on the vanadia content and the preparation technique [27][28][29][30][31][32][33][34]. At vanadia content below 10 % of monolayer (ML), only a monomeric isolated structure exists, which has a tetrahedral coordination (VO 4 ) in dehydrated conditions [29,33].…”
Section: Introductionmentioning
confidence: 99%
“…4 shows Raman spectra (solid line) of both dehydrated HE-FSP-made 10V40-16 and impregnated (10V65-9 imp, 10V40-16 imp) V 2 O 5 /TiO 2 . The flame-made catalyst exhibited a clear band at 1033 cm −1 that corresponds to monomeric VO x species [13]. as well as a band at 940 cm −1 confirming the presence of amorphous polymeric VO x species [32] stemming from the higher V coverage (16 V nm −2 ) of HE-FSP-made particles.…”
Section: Influence Of Preparation Variables On Structural Properties mentioning
confidence: 86%
“…The band at around 800 cm −1 stems from the Si-O-Si vibration of the quartz window used in the in situ cell. At very low V coverage (1 V nm −2 , 1V93-1), a V=O stretching band at 1032 cm −1 attributed to monomeric VO x [13] was detected. With increasing V coverage up to 15% (w/w) V 2 O 5 , a band at around 920-940 cm −1 appeared that can be attributed to the V O-V bridges of the polymeric VO x species [6,17,[32][33][34][35].…”
Section: Influence Of Preparation Variables On Structural Properties mentioning
confidence: 99%
See 1 more Smart Citation